Victim of its own success: how NATO's difficulties are caused by the absence of a unifying existential threat. (2nd January 2018) - Viggo Jakobsen, Peter; Ringsmose, Jens
Abstract : NATO is neither in deep trouble nor destined to fall apart. The 'NATO-in-crisis perspective', which has gained currency in recent years, correctly identifies three centrifugal forces that threaten to undermine the Alliance: strategic divergence, a declining ability to act militarily and fading public support. These problems are partly of NATO's own making because they stem from the creation of a generally benign security environment devoid of clear and present existential threats. While the absence of a clear, unifying existential threat has made it impossible for the Alliance to agree on a common core purpose, this does not mean that NATO will fall apart. Three centripetal forces that will continue to keep it together trumps the three centrifugal forces identified by the NATO-in-crisis perspective: converging national security interests, a strong sense of community and US leadership.